Síntese e caracterização de cintiladores de aluminossilicatos nanoestruturados, dopados com Ce3+, Eu3+ e Mn2+ - Teixeira, Verônica de Carvalho (2014)
In the present work a new synthesis route, a hybrid between solid state reaction and proteic sol-gel method, is applied to a scintillator material based on Ca2Al2SiO7 (CAS). The luminescence mechanisms for the nanostructured scintillator is studied a mechanism that describes the luminescence process, when excited with X-rays, is proposed. The same system was also prepared via other 2 different methodologies, solid state traditional route, proteic sol-gel route, and 3 different solvents were used, for comparison in the hybrid method. In all cases the CAS phase was found as indicated by X-ray powder diffraction. During the thermal evolution of CAS precursors prepared via hybrid route assisted by coconut water, intermediate oxide phases were formed and they reacted with SiO2 to form the final CAS phase. SEM images indicated that the organic molecules present in the coconut water play an important role in the nanoparticle formation defining the average size and morphology, Samples prepared via the hybrid route showed particle with spherical shape with average size of (36 ± 15) nm. Analysis carried out via photoemission spectroscopy indicated that Si ions are the most abundant cation on surface of the particles produces via hybrid methods and solid state reaction. X-ray absorption (XAS) revealed that the Si coordination environment did not change during the synthesis. The XAS technique also indicated that the main valence for the dopants in CAS structure and the emission spectra obtained via pholuminescence and X-ray excited optical luminescence (XEOL) confirmed that the main emissions are related to the dopants on the CAS matrix. Extended X-ray absorption fine structure revealed the location of the dopants in the CAS matrix, and the most probable defect generated for the dopant presence. XEOL excitation spectra showed different behaviors for the luminescence around K edge of the matrix elements. The XEOL decay time indicated that fast scintillators were produced when CAS were doped with Ce3+ with characteristic constants lower than 40 ns. The results time dependent XEOL emission also showed that the luminescence decay curves are influenced by the presence of electrons and holes shallow traps in the CAS electronic structure.